Liability of Lessees and Assignees of Commercial Leases in New Zealand - Tait, Emma (Victoria University of Wellington Law Review, 2008)
This article concerns the liability of lessees and assignees of commercial leases in New Zealand. This is a complicated area of the law and, as an analysis of the historical context shows, one that was ripe for reform. The Property Law Act project which culminated with the enactment of the Property Law Act 2007 provided an opportunity to undertake this reform. However, this article shows that the resulting Act not only fails to correct existing deficiencies in this area but also places an increased burden on assignees that cannot be justified by reference to privity of contract or privity of estate.